Resveratrol and N-acetylcystein reduce hepatic steatosis but enhance initiation and progression of hepatocellular carcinoma by inhibiting GST-pi-MAPK axis in mice - Zhang, Mi; Yuan, Weigang; Li, Chun; Chen, Chanyuan; Liu, Xiang; Ma, Zhilu; Xiang, Yifei; Chen, Guisha; Wang, Chunxu; Li, Lei; Wang, Lingli; Xu, Zhong; et al. (Frontiers in Pharmacology, 2025)
IntroductionAccumulating evidence indicates that antioxidants promote tumor growth and metastasis after tumor onset in several cancer types. However, whether antioxidants prevent or accelerate hepatic tumorigenesis during steatosis remains unknown. Therefore, we investigated the effects of resveratrol (RES) and N-acetylcysteine (NAC) on hepatocellular carcinoma (HCC) development using two fatty liver mouse models.MethodsHigh-fat diet (HFD) plus diethylnitrosamine (DEN)- and AKT/Ras-induced primary HCC mouse models were used. The weight, liver weight ratio and the number of HCC tumors were calculated and histological features of mouse HCC tissues were analyzed using immumohistochemical staining such as hematoxylin and eosin staining. Proteomic analysis was used to screen for differences in liver cancer progression between antioxidant-treated HCC and models. Protein inhibitor recovery experiments in mice and in vitro cells validate the targets screened by proteomic analysis. The expression of GST-pi, p-JNK and p-p38 signaling molecules in HCC were investigated using Western blotting.ResultsRES and NAC enhance HCC formation in both DEN/HFD and AKT/Ras mice. RES and NAC alleviate hepatosteatosis, and reduce ROS and DNA damage in mice. Proteomic analysis and protein inhibitor recovery assay demonstrated that GST-pi is a therapeutic target for antioxidant-induced hepatocellular carcinoma growth. Mechanistically, RES and NAC decreased p-JNK and p-p38, the two major mitogen-activated protein kinases, in HCC cells. Blockade of GST-pi abrogated the reduction in p-JNK and p-p38 levels and increased apoptosis of HCC cells.ConclusionAntioxidants may increase the incidence of HCC in a population with fatty liver, despite reduction in ROS production, by inhibiting GST-pi-MAPK axis.